The Tin Euphoria Paradox: A Psychosocial Analysis Of Low Educational Retention Among Adolescents In Belitong Island - Muhammad Belva Juliadi (jfpublisher, 2026)
The tin mining industry in Belitung Island, Bangka Belitung Islands Province, has long produced a sociocultural paradox in which immediate economic rewards systematically weaken adolescent commitment to formal education, contributing to persistent school dropout rates and a disproportionately high prevalence of early marriage. This study examines the psychosocial dynamics underlying both phenomena, focusing on how mining culture, psychological vulnerability, and cultural normalization collectively generate measurable consequences among school-aged adolescents. A descriptive qualitative method with a case study approach was applied, integrating structured field observations with secondary data analysis obtained from the Central Bureau of Statistics (BPS) and the National Population and Family Planning Board (BKKBN), while data validity was secured through triangulation techniques. The findings indicate that school dropout in Belitung Island functions as a product of structural violence, in which the tin mining economic system indirectly removes adolescents from formal education through instant gratification mechanisms, as neurologically vulnerable adolescents consistently prioritize short-term mining income over long-term educational investment. This condition further drives elevated early marriage rates, recorded at 18.76 percent in 2020, representing nearly double the national average, with women bearing a disproportionate psychological burden that includes anxiety, depression, and identity foreclosure. Most substantially, the widespread community normalization of both dropout and early marriage has established a self-perpetuating cycle of learned helplessness that proves resistant to institutional intervention, indicating that resolution demands not only regulatory reform but a foundational shift in local values that genuinely repositions education as a pathway toward sustainable prosperity.